(untitled) (European Journal of Marketing and Economics, 2018)
The attraction of foreign direct investment for years has been on focus of many governments around the world. These governments try to draft their policies in order to compete in attracting this important source to their development. The design of successful policies requires good understanding of the motives that a foreign investor would bring to the host country. Using different literature on Foreign Direct Investments, this paper analyzes multinational theories, which explain why a company decides to serve the foreign market and does not prefer export or licensing. The paper also reviews broad literature on the determining factors of host countries, which constitute an important moment in the decision of multinational companies for the host country of their direct investment.